La investigación formativa sobre biodiversidad en la Institución Educativa Técnico Agrícola de Boavita : aportes para su didáctica - Rincón Bello, Zully Tatiana (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Eng: Biological diversity from the school requires not only a curricular transformation, it also implies a pedagogical deconstruction where the praxis is based on responding to the learning needs of the students, it is there that research becomes a tool that will allow the articulation of its didactic components. Therefore, a formative research strategy was carried out around biodiversity with the students of the Boavita Agricultural Technical Educational Institution that would make it possible to energize the didactic components of the concept. Based on the contextual characterization of the students' previous ideas about biodiversity, a research hotbed was developed and implemented in order to consolidate the research strategy; which was evaluated with 13 sixth and seventh grade students using the results of a pre-test and post-test, which showed an increase in appropriate behaviors towards biodiversity after the application of the strategy. From the students' discourse, obtained from the 13 interviews, the relationship of some conceptual categories was evidenced that allowed contributions to the didactics of biodiversity from the classroom. This allowed us to conclude that the incorporation of formative research in the school, from the research hotbeds, strengthens the study of biodiversity at various scales, since it allows students and teachers a greater understanding of the concept in a systemic way, in addition to fostering a behavioral change in the face of the conservation of biological resources and finally allows the articulation of the didactic components.